2020
DOI: 10.1136/rmdopen-2020-001223
|View full text |Cite
|
Sign up to set email alerts
|

Impact of skin, musculoskeletal and psychosocial aspects on quality of life in psoriatic arthritis patients: A cross-sectional study of outpatient clinic patients in the biologic treatment era

Abstract: BackgroundIn psoriatic arthritis (PsA), both psoriasis and musculoskeletal manifestations may impair Health-Related Quality of Life (HRQoL). Our objective was to explore the impact of the various disease manifestations and disease consequences, including psychosocial factors, on HRQoL in PsA patients treated in the biologic treatment era.MethodsData collection in the 131 outpatient clinic PsA patients assessed included demographics, disease activity measures for both skin and musculoskeletal involvement and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…In the present study, we wanted to explore the single elements that may impact sleep, fatigue, and depression in PsA. Thus, we excluded HRQoL measures, composite disease activity scores, and global scores both investigator and patient global assessment which previously has been reported [11,13].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we wanted to explore the single elements that may impact sleep, fatigue, and depression in PsA. Thus, we excluded HRQoL measures, composite disease activity scores, and global scores both investigator and patient global assessment which previously has been reported [11,13].…”
Section: Methodsmentioning
confidence: 99%
“…May ↑ risk of infection Do not initiate in pts with any clinically important active infection until it has resolved or been adequately treated (EU, USA); consider risks and benefits before initiating in pts with a chronic infection or past recurrent infection (USA) Instruct recipients to seek medical advice if they experience signs/symptoms of a clinically important infection (chronic or acute); closely monitor any pt who develops a serious or clinically important infection (or is not responding to standard therapy) and discontinue guselkumab until infection [20,21]. Patients with psoriatic arthritis typically report reduced HR-QOL relative to the general population [33], with contributing factors including the psychosocial burden, impaired physical function and comorbidities associated with the condition [34]. Guselkumab provides durable clinical benefits based on results through two years of treatment in clinical trials [23,30].…”
Section: Infectionsmentioning
confidence: 99%
“…Interestingly, increased peripheral inflammatory markers were more common among anti-depressant non-responders compared with responders. 8 Furthermore, it is well 2846 (28) 3813 2531 291 257 226 174 215 (2) Other csDMARDs (%) 205 (11) 703 (7) 649 4382 (27) 929 (21) 366 (14) 166 (8) 292 (8) 74 7bDMARDs (17) 1554 (15) 2095 (14) 338 (24) 972 (22) 409 (16) 180 (8) 410 (11) 97 (10) Glucocorticoids (%) (12) 2394 (23) 3988 (26) 143 (10) 834 (19) 591 (23) 235 (11) 673 (18) 208 (21) bDMARD, biologic DMARD; cDMARD, conventional synthetic DMARD; DMARD, disease modifying anti-rheumatic drugs; TNF, tumour necrosis factor. 281 (6) 310 (5) 193 (17) 370 (12) 134 (10) 406 (20) 471 (14) 119 (13) Female (%)…”
Section: Discussionmentioning
confidence: 99%
“…So far, metaanalyses and cohort studies have shown higher odds for depression among patients with RA, PsA and AS [19][20][21][22] compared with the general population. Depression in rheumatic diseases has been associated with impaired health-related quality of life, 23 worse response to treatment and lower improvement in disease activity over time. 8 12 24 Only few small cohort studies have directly compared the OR of depression between different IRDs, reporting an equal probability between patients with AS and RA 25 and a higher probability in patients with PsA compared with RA.…”
Section: Inflammatory Arthritismentioning
confidence: 99%